Functionalized Bark for Recycled Polypropylene-Based Composites (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
A new method for the modification of the bark surface using N,N-diethyl-2,3-epoxypropylamine (DEEPA) was developed. As a result, the part of the bark phenolic hydroxyl groups were replaced with amine groups. The conditions of the modification were found, and the modified products were analysed. The different amount of the introduced amino groups in hardwood and softwood bark was gained by the various contents of lignin in the wood species. The recycled propylene-based composites filled with the modified bark were characterised by higher mechanical parameters in comparison with the composites filled with unmodified bark. The differences in the mechanical properties of the polymer composites filled with softwood - pine (Pinus sylvestris) bark and hardwood - grey alder (Alnus incana) bark has been established.